Werner Kofler Kommentierte Werkausgabe, Bd. V (2023)
Volumes I to III of the Annotated Edition of Werner Koflers Works gather radio plays, poetry (exemplary), short prose, and dramatic texts. A detailed commentary on passages and a comprehensive bibliography complete the two volumes, that are showing hitherto lesser-known sides of Kofler's œuvre.